PENGARUH MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR PKN DI SDN SUMBEK LOMBOK TENGAH - Yuliani, Meri; Habibi, Muhamad Ridwan; Irawan, Darmi (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to determine the effect of implementing the TPS (Think, Pair, Share) learning model on the Civics learning outcomes of fifth grade students at Sumbek State Elementary School, Central Lombok. This research uses an experimental design in the form of True Experimental Design Type Pre test-Post test Control Group Design with one type of treatment using an experimental class and a control class. The sampling technique uses a total sampling technique (entire sample). The data collection technique uses the Civics learning outcomes test method. The data analysis technique uses the t-test to test the effect of implementing the TPS learning model on Civics learning outcomes. The results of this research show that the calculated average post test score for the experimental class was 83.29, higher than the average for the control class, which was 77.37. The results of data analysis show that the calculated t value is 3.200 > t table 2.013. This means that there is a significant difference between the post-test results of the experimental class which used the TPS learning model and the control class which did not use the learning model. This can be interpreted as meaning that learning that uses the TPS learning model has higher learning outcomes compared to learning that does not use the learning model. Thus, it can be concluded that there is a positive influence of the application of the TPS learning model on the Civics learning outcomes of class V students at Sumbek State Elementary School, Central Lombok.